2005
DOI: 10.1021/ja052804q
|View full text |Cite
|
Sign up to set email alerts
|

Dual Lewis Acid−Lewis Base Activation in Enantioselective Cyanation of Aldehydes Using Acetyl Cyanide and Cyanoformate as Cyanide Sources

Abstract: Dual activation by a chiral Lewis acid and an achiral or chiral Lewis base enabled cyanation of both aromatic and aliphatic aldehydes with acetyl cyanide and ethyl cyanoformate to provide direct access to O-acetylated and O-alkoxycarbonylated cyanohydrins, respectively, under mild conditions. With a combination of a Ti-salen catalyst and Et3N, benzaldehyde was converted to the O-acetylated cyanohydrin with 94% ee within 10 h at -40 degrees C in 89% isolated yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(82 citation statements)
references
References 18 publications
2
75
0
2
Order By: Relevance
“…Cinnamoyl cyanide (2g) was the most reactive ketonitrile and gave the acetylated product in high isolated yield with excellent ee after only four hours (entry 7). Benzoyl cyanide (2h) provided the product with high isolated yield and good ee (76 % yield and 75 % ee 1 [17] 3a [C 6 H 5 ] 1a 10 89 94 (S) 2 [17] 3b [4-CH 3 -C 6 H 4 ] 1b 10 90 96 (S) 3 [17] 3c [4-CH 3 O-C 6 H 4 ] 1c 12 72 94(S) 4 [17] 3d…”
Section: Asymmetric Synthesis Of Cyanohydrin Estersmentioning
confidence: 99%
“…Cinnamoyl cyanide (2g) was the most reactive ketonitrile and gave the acetylated product in high isolated yield with excellent ee after only four hours (entry 7). Benzoyl cyanide (2h) provided the product with high isolated yield and good ee (76 % yield and 75 % ee 1 [17] 3a [C 6 H 5 ] 1a 10 89 94 (S) 2 [17] 3b [4-CH 3 -C 6 H 4 ] 1b 10 90 96 (S) 3 [17] 3c [4-CH 3 O-C 6 H 4 ] 1c 12 72 94(S) 4 [17] 3d…”
Section: Asymmetric Synthesis Of Cyanohydrin Estersmentioning
confidence: 99%
“…After completion of the reaction, the product was purified by flash column chromatography on a silica gel column (eluent, hexane/ethyl acetate 5 90:10). The purified products were characterized by 19,59,60 Earlier, we 58 and others 46,48,49 have reported that the presence of a cocatalyst greatly influence the chiral metal complexes catalyzed enantioselective addition of ethylcyanoformate to aldehydes. The cocatalysts used so far for this reaction are essentially organic bases and are nonrecoverable after the catalytic run is over.…”
Section: Typical Experimental Procedures For the Enantioselective Cyanmentioning
confidence: 99%
“…As a result, currently, other sources of cyanide such as acetyl cyanide, cyanoformate esters (ROCOCN), diethyl cyanophosphonate, and benzoyl cyanide have been explored to prepare optically pure cyanohydrins with different catalytic systems. Belokon et al, 40 has reported the ethyl cyanoformylation of aldehydes using Ti(IV) salen complex (5 mol %) as catalyst at 2408C giving the product in high yield with excellent enantiomeric excess (ee) in 6-48 h. Later, Moberg and coworkers 48 have significantly reduced the time (4-12 h) for this reaction in the presence of various Lewis bases as co-catalyst best among which was found to be triethylamine. Feng and coworkers 56 undertook cyanoethoxycarbonylation of aldehydes catalyzed by heterobimetallic aluminum lithium bis(binaphthoxide) and cinchonine to give the product in excellent yield (up to 99%) with moderate to high enantioselectivity (up to 95% ee) in short time.…”
Section: Introductionmentioning
confidence: 99%
“…Moberg and coworkers also achieved the highly enantioselective cyanation of aldehydes by using the dual activation concept (Table 4.5) [30]. It is known that the Lewis acidic dimeric salen-Ti complex 8 catalyzes the cyanation of benzaldehyde with trimethylsilyl cyanide [31].…”
Section: Cyanohydrin Synthesismentioning
confidence: 99%